2015
DOI: 10.1186/s12937-016-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of coffee consumption on self-reported gastrointestinal symptoms, blood pressure and stress indices in healthy individuals

Abstract: BackgroundIt has been suggested that coffee may affect the gut-brain axis with conflicting outcomes. Moreover, there is insufficient evidence to determine whether the type or temperature of coffee consumed will have a different impact on the gut-brain axis. The purpose of this study was to investigate the effects of acute coffee consumption on the following: 1. self-reported GI symptoms and salivary gastrin, 2. stress indices [salivary cortisol and alpha-amylase (sAA)] and psychometric measures, and 3. blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 69 publications
1
28
3
3
Order By: Relevance
“…(20) In a study by Emelia Papakonstantinon, Ionna Kachribari did not find any significant association between coffee consumption and acid peptic disease. (21) In our study, we could not find out any relationship between non vegetarian diet and acid peptic disease. (21) But in a comparative study by Jung J G, Kang H W et al among Buddhist priests and general population established a significant association between non vegetarianism and acid peptic disease.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…(20) In a study by Emelia Papakonstantinon, Ionna Kachribari did not find any significant association between coffee consumption and acid peptic disease. (21) In our study, we could not find out any relationship between non vegetarian diet and acid peptic disease. (21) But in a comparative study by Jung J G, Kang H W et al among Buddhist priests and general population established a significant association between non vegetarianism and acid peptic disease.…”
Section: Discussioncontrasting
confidence: 65%
“…(21) In our study, we could not find out any relationship between non vegetarian diet and acid peptic disease. (21) But in a comparative study by Jung J G, Kang H W et al among Buddhist priests and general population established a significant association between non vegetarianism and acid peptic disease. (22) Similarly a study by Syed Faisal Zaidihad established a relationship between a non-vegetarian diet and acid peptic disease.…”
Section: Discussioncontrasting
confidence: 65%
“…These drinks contain 3784 mg, 1514 mg, and 404 mg caffeine, respectively. 17,18 Data acquisition Electrocardiogram recordings were obtained from the participants for 5 minutes in rest and sitting position. Disposable Ag-AgCl electrodes were placed following the Einthoven triangle configuration.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Subjects (44.4%) in the control group and subjects (27.8%) in the intervention group had a habit of drinking coffee. Papakonstantinou et al (2016) reported coffee consumption significantly increased BP 3 hours post-consumption without differences between coffee types, and temporary hypertensive coffee effect occurred even after small doses of consumed caffeine (80 mg/day). The type of coffee consumed may have a different impact on BP suggesting that boiled coffee may cause a higher increase in BP compared to filtered coffee, after daily consumption of large coffee doses (>5 cups) for several days or weeks.…”
Section: Habits Of the Subjectsmentioning
confidence: 99%